BUROCRACIA COMO ORGANIZAÇÃO, PODER E CONTROLE - Francis Kanashiro Meneghetti; José Henrique de Faria (RAE: Revista de Administração de Empresas, 2011)
The main objective of this work is to analyze the way in which Maurício Tragtenberg and Fernando Cláudio Prestes Motta conceivedbureaucracy. The specific objectives are: to understand the main characteristics of bureaucracy according to Weber, the author who hasmost influence on the work of Tragtenberg and Prestes Motta; to arrive at an understanding of bureaucracy as expressed in the work ofTragtenberg, to learn how bureaucracy is understood in the work of Prestes Motta and to analyze the relationships that exist betweenthe understanding of bureaucracy in Tragtenberg and Prestes Motta. In analyzing the authors consideration was given to their concept ofbureaucracy, their intellectual trajectory, the order of their production, epistemologies, space and historical time, the semantic, ideological and cultural dimension and questions that are important for an understanding of the theoretical development of the concept. The conclusion was reached that, despite the differences in the intellectual paths of Tragtenberg and Prestes Motta, bureaucracy is understood by both as being organization, power and control